الكسب الثنائي لحروف المعاني )حروف الخفض في سورة البقرة نموذجا( - Zanuar Anwari (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
When we shed light in the study of the Arabic language, we find that the letters of meanings are one of the most important tools used in sentence structure. Although the use of these tools in the sentence was not a conditional pillar in its formulation, it did not lose its importance in expressing the different circumstances surrounding the event .This article was an attempt to objectively find out the use of the letters of meaning, especially the letters of abbreviation or preposition, with all the various meanings carried by the expressions of the Qur’an. It is the longest surah of the Qur’an and is presented in the order of the Qur’an .At the end of his research, the writer came to the conclusion he drew through his study of these tools. Among them is that the letters of meanings, and we mention, for example, the letters of preposition, were used in this surah more than a thousand times, and the various meanings referred to by these letters may lead to dual meanings.This matter indicates the richness of this language, especially when choosing its expressions in the words of the Qur’an to express the various events that add to the researcher’s attraction and admiration.